Study on the similarity of wet gas pressure drop in long-throat Venturi. (August 2019) - Wu, Haitao; Xu, Ying; Wang, Jinghan; Zhang, Tao; Wang, Huaxiang
Abstract: This study investigates the effect of pipe diameter on pressure drop with the same diameter ratio, similar pressure-sampling position and throat length of long-throat Venturi. Considering the factors including the void fraction, the friction between the two phases and the entrainment in the gas core, the one-dimensional momentum equation for gas has been solved in the axial direction of long-throat Venturi. A novel void fraction model is established, by considering the effects of dryness and gas-liquid density ratio, then predicting the distribution of wet gas static pressure between the two pressure tapings of the long-throat Venturi. The comparison between the values predicted by the model and those measured experimentally reveals that all the relative deviations of the predicted points by the modified model were within ±15%. In the same entrance conditions, the effect of pipe diameter on pressure drop in long-throat Venturi is similar. Highlights: The pressure drop includes accelerated, frictional and entrained pressure drop. Model for predicting the void fraction of Venturi is obtained. Experimental data and model prediction prove that the Venturi has a strong geometric similarity.